THE SECRETS TO MASTERING ACADEMIC WRITING SKILLS: FORMAL STYLE, CRAFTING A STRONG THESIS STATEMENT, AND RULES FOR AVOIDING PLAGIARISM. - Ravshanova Marjona Jumaniyoz qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT: This article provides essential strategies and actionable rules for students and researchers aiming to elevate their academic writing skills to meet international standards. Effective academic communication requires a balance between formal language, clear argumentation, and unwavering integrity. The paper first explores the principles of Formal Style, emphasizing the necessity of objectivity, clarity, and the judicious use of sophisticated academic vocabulary, while advising against personal pronouns and emotional language. Next, it delves into the core of any scholarly work: the Thesis Statement. Practical guidelines are offered on how to craft a thesis that is debatable, specific, and focused, serving as the central argument of the entire paper. Finally, the article provides a critical review of Rules for Avoiding Plagiarism, distinguishing between direct quoting, effective paraphrasing, and summarizing. It underscores the importance of proper in-text citation using recognized formats (e.g., APA/MLA) to uphold academic honesty. By mastering these three pillars—formal expression, strong argumentation, and ethical referencing—authors can ensure their research is not only impactful but also credible and academically rigorous.